DISASTER IN SOCIOLOGICAL PERSPECTIVE - Dhanny Septimawan Sutopo (Institut Pendidikan Tapanuli Selatan, 2023)
Various quite extreme natural disasters have hit various parts of the world this year. Starting from America, China, Indonesia to Greece and Spain. Even Al Jazeraa re-wrote the list of disasters that occurred in a long list in early November, 2021. There has been a change in the orientation of disaster studies in the last decade, if initially discussing more technical issues about disaster triggering events and handling disaster victims, an approach that emphasizes more on human and community approach. In this study, trying to provide an overview of the sociological perspective of disaster management, which discusses the diversity of understanding, responses and patterns of local communities in dealing with disasters as well as understanding, responses and patterns of external actors or organizations in disaster management. Disaster planning and preparedness activities are a continuous learning process, not an end goal. The sociological perspective is not just knowledge, but must be a guide in the preparation of programs of activities, priorities, and strategies for implementing sustainable disaster management. Keywords: Disaster, Sociological Perspective, Disaster Management